AN ANALYSIS OF THE STUDENTS’ ERROR IN USING CONJUNCTION IN WRITING ABSTRACT OF THESIS - Velen Yanterka; Loli Safitri, Syahrul, Hilma Pami Putri (Indonesian Journal of Education (INJOE), 2023)
This research was due to some problems found in thesis abstract of the students who graduated from English Education Department of UIN Bukittinggi. First, the students do not place the conjunction correctly in their thesis abstract. Second, the students do not understand which conjunction is proper for their abstract to be cohesive. Furthermore, the purpose of this research was to find out type of conjunction error that students made in writing their thesis abstract. The researcher used qualitative research design. Furthermore, to choose the research subject for this study, the researcher applied the approach of purposeful sampling. Then, the subject of the research was the undergraduate theses of the students which is 23 theses. Then, the instrument that was used in a research was documentation checklist. Based on the result of the research, the researcher concluded that there were 2,56% addition error, 43,59% omission error, 50% misformation error, and 3,85% Misordering error. Furthermore, the researcher concluded that the most frequent conjunction error was misformation error, followed by omission error, Misordering error, and addition error. It makes the most frequent error is misformation error and the least frequent error is addition error.